Characteristics of the extracellular polymeric substance composition in an up-flow biological aerated filter reactor: The impacts of different aeration rates and filter medium heights. (October 2019) - Ren, Jiehui; Cheng, Wen; Wan, Tian; Wang, Min; Meng, Ting; Lv, Taotao
Graphical abstract: Highlights: Aeration rates affect the compositions and contents of EPS. Increase in the LB-EPS and TB-EPS contents could increase biofilms adhesion. Protein-like substances are consistently more dominant than humic-like substances. Humic-like substances show significant positive correlation with the microbes. Abstract: In this study, the compositional characteristics of extracellular polymeric substances (EPS) were systematically explored to reveal their relationship with microbial community under different conditions in an up-flow biological aerated filter reactor. The aeration rates had a significant positive correlation (0.898 ≤ R ≤ 0.979) with the tightly bound (TB)-EPS contents, but basically showed an opposite trend (R < −0.631) with the loosely bound (LB)-EPS. Moreover, the filter medium heights also affected EPS distribution. The microbial biofilm produced more LB-EPS and TB-EPS to withdraw from the extreme environment. Five fluorescent substances were identified in the EPS by EEM-PARAFAC modeling; namely, two protein-like components (protein-like C1 and tryptophan-like C2) and three humic-like components (UVA marine humic-like C3, hydrophobic humic acid-like C4, and humic acid-like C5). Under different conditions, the relative abundance of Proteobacteria and Nitrospirae had a significant positive correlation with C5 and C4, respectively. These results demonstrated that microbial community distribution could affect EPS composition.